Experimental study on depolarized GAWBS spectrum for optomechanical sensing of liquids outside standard fibers - Hayashi, Neisei; Mizuno, Yosuke; Nakamura, Kentaro; Set, Sze Yun; Yamashita, Shinji (Optics express, 2017)
We report an experimental study on the spectral dependence of depolarized guided acoustic-wave Brillouin scattering (GAWBS) in a silica single-mode fiber (SMF) on acoustic impedance of external materials. The GAWBS spectrum was measured when the acoustic impedance was changed from 1.51 to 2.00 kg/s·mm . With increasing acoustic impedance, the linewidth increased; the dependence was almost linear with an acoustic impedance dependence coefficient of 0.16 MHz/kg/s·mm . Meanwhile, with increasing acoustic impedance, the central frequency linearly decreased with an acoustic impedance dependence coefficient of -0.07 MHz/kg/s·mm . These characteristics are potentially applicable to acoustic impedance sensing.